Pharmacokinetics, Safety, and Tolerability of Lasmiditan in Pediatric Patients with Migraine - Tsai, Max; Nery, Emel Serap Monkul; Kerr, Lisa; Khanna, Rashna; Komori, Mika; Dennehy, Ellen B.; Wilbraham, Darren; Winner, Paul (Clinical pharmacokinetics, 2021)
Introduction Lasmiditan is a selective serotonin (5-HT1F) receptor agonist approved in the US for the acute treatment ofmigraine in adults. This phase I, open-label, two-cohort study assessed the pharmacokinetics (PK), safety, and tolerability of lasmiditan in patients with migraine aged 6 to < 18 years. Methods Cohort 1 (15 to ≤ 40 kg) and Cohort 2 (> 40 to ≤ 55 kg) received single oral doses of lasmiditan (100 mg and 200 mg, respectively).Blood samples for the assessment of PK and safety parameters were collected over a 24-h period. Follow-up was approximately 14 days after dosing. Results Eighteen patients received lasmiditan (11 in Cohort 1, 7 in Cohort 2) and 17 patients completed the study. One patient in Cohort 2 discontinued due to adverse events. Plasma concentrations peaked at 1.5–2 h post dose and then declined, with a terminal half-life of approximately 4 h in both cohorts. While the exposure to lasmiditan was generally similar between cohorts, PK parameters, such as apparent total body clearance and volume of distribution, were greater for the 200 mg cohort relative to the 100 mg cohort. No deaths or serious adverse events were reported. The frequency and severity of adverse events (including somnolence, dizziness, and fatigue) were generally mild and similar to those in adult studies. Conclusion: The PK results support weight-based dosing of lasmiditan in pediatric patients with migraine and no new safety or tolerability issues were identified. These findings support further investigation of lasmiditan as a potential treatment in pediatric patients with migraine. Clinical Trial Registration Numbers NCT03988088 and EMEA-002166-PIP01-17M02.